Login
Remember
Register
Home
All Activity
Q&A
Questions
Hot!
Unanswered
Tags
Categories
Users
Ask a Question
Ask a Question
Using `a^2 – b^2 = (a + b) (a – b)`, find `(1.02)^2 –
0
votes
asked
Jan 18, 2022
in
8th-maths
by
yogita
(
1.8k
points)
Using `a^2 – b^2 = (a + b) (a – b)`, find
`(1.02)^2 – (0.98)^2`
marks2
chapter9
#sub
Please
log in
or
register
to answer this question.
0
Answers
Categories
All categories
Maths
(8.6k)
12th-maths
(0)
11th-maths
(0)
10th maths
(0)
9th-maths
(0)
8th-maths
(8.6k)
Science
(14)
Physics
(3.4k)
Related questions
Using `a^2 – b^2 = (a + b) (a – b)`, find `(1.02)^2 –
Using `a^2 – b^2 = (a + b) (a – b)`, find `(1.02)^2 –
Using `a^2 – b^2 = (a + b) (a – b)`, find `12.1^2 –
Using `(x + a) (x + b) = x^2 + (a + b) x + ab`, find `5.1 xx 5.2`
Using `a^2 – b^2 = (a + b) (a – b)`, find `12.1^2 –